THE EFFECT OF HYDROLOGICAL CONDITIONS ON THE BEHAVIOR OF WINTERING HERRING IN THE SOUTHWESTERN PART OF THE NORWEGIAN SEA (O Vliyanii Gidrologicheskikh Uslovii na Povedenie Zimuyushchei Seldi v Yugozapadnoi Chasti Norvezhskogo Morya) - Pakhorukov,V. I. (1970)
A relationship between the distribution of herring in winter and the temperature conditions in the NW part of the Norwegian Sea was established. In cold years the pre-spawning concentrations of herring occur south of 65 degrees N, whereas in warm years they occur north of the latitude. In temperature and warm years, individuals with gonads in stages IV-V and V predominate in December, but in cold years individuals with gonads in stage IV predominate. On the basis of sampling carried out it is possible to forecast in October the amplitude of vertical diurnal migration for the entire winter in mixed water of the East Iceland Current. It is known that herring reaches depths where the water temperature is near 0. Water with negative temperature may in cold winters rise as high as 150-90m from sea level, but at times when the East Iceland Current flaters and the warm Atlantic water crosses the Faroes-Iceland Threshold, the 0 isotherm lies at a depth of 350-420m. If the depth of a water layer with negative temperature is known for October, the depth reached by herring in diurnal migrations in November - December can possibly be determined. This information aids in improving the quantity of herring catches in deep water. Consequently, it is possible to forecast in October the concentration places of herring for the subsequent two months. Trans. of Polyarnyi Nauchno-Issledovatelskii Institut Morskogo Rybnogo Khozyaistva i Okeanografii. Trudy (USSR) n12 p83-86 1968, by M. Slessers.